Bibliometric Study: Writer's Productivity According to Lotka's Law in The Edulib Journal Publication Year 2011 – 2021 - Wahyudi, Agus; Junaedi, Jusa (Edulib, 2023)
This research is a bibliometric study using Lotka's Law. Lotka's Law describes the frequency of publications by authors in a particular field. According to Lotka, there is an inverse relationship between the number of articles written and the number of authors who write articles, namely the more articles written, the fewer authors write them. This research aims to determine the pattern of writer productivity according to Lotka's law in the Edulib journal. The object of this research is articles in the Edulib journal with a publication period of 2011-2021. The data collection method in this research was carried out by documentation and then tabulated in table format using MS Excel. Article obtained from the page https://ejournal.upi.edu/index.php/edulib/issue/archive. The articles collected were 166 articles written by 206 different authors. In this research, the "Straight Count" technique was used, namely only the main author or first author was counted. Because there are 79 authors as second authors, the number of authors calculated is 127. The calculation results show that the parameter value n is 2.6895 and C is 0.7985. This means that in 2011-2021 the number of authors who contributed one article was 79.85% of the total number of authors. The results of this research also show that the largest number of author collaborations is five authors in producing one article. The author listed as the first author who was most productive in producing articles was Doddy Rusmono with a contribution of 6 articles.